CROSSFIRE/CRFB, Deutschland „Crossing Frontiers in Iron Age and Roman Europe (CROSSFIRE )“ und Corpus der römischen Funde im europäischen Barbaricum - Voß, Hans-Ulrich (e-Forschungsberichte des DAI, 2023)
In the research field 2 „CROSSing Frontiers in Iron Age and Roman Europe“, the edition of archaeological material in the „Corpus of Roman finds in the European Barbaricum“ is being continued with the first part of the volume “Freistaat Thüringen. Nord- und Ostteil”. It contains findings that are of key importance not only for our understanding of Romano-Germanic relations during the occupation under Augustus and Tiberius (Großromstedt), the period of the „crisis of the 3rd century“ with the „Gallic Empire“ [AD 260-274] (e.g. Dienstedt, Haßleben, Nordhausen) and the Late Roman period (Großbodungen); a large-scale synopsis also provides a clear assessment of relations between indigenous groups outside the Roman Empire in the light of Roman finds and influence.